The Strange Alchemy of Life and Law. - Sachs, Albie (OUP Oxford, 2009)
From a young age Albie Sachs played a prominent part in the struggle for justice in South Africa. As a result he was detained in solitary confinement, tortured by sleep deprivation and eventually blown up by a car bomb which cost him his right arm and the sight of an eye. His experiences provoked an outpouring of creative thought on the role of law as a protector of human dignity in the modern world, and a lifelong commitment to seeing a new era of justice established in SouthAfrica. After playing an important part in drafting South Africa's post-apartheid Constitution, he was appointed by Nel.